Pengaruh Lingkungan Kerja dan Keterampilan Komunikasi Terhadap Kinerja Karyawan di HW Hotel Padang - Suharjadi Wahyu; Pasaribu Pasaribu (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the influence of the work environment and communication skills on employee performance at HW Hotel Padang. The research method used is a quantitative approach with an associative research design. Data were collected through the distribution of questionnaires to 57 respondents who are employees of HW Hotel Padang. The results of the study show that both the work environment and communication skills have a significant effect on employee performance. The majority of respondents gave positive responses regarding the condition of the work environment and communication skills in the workplace. Furthermore, communication skills were found to have a more dominant influence than the work environment in improving performance. This study highlights the importance of creating a conducive work environment and enhancing communication skills as strategic efforts to improve employee performance in the hospitality industry.